The recurrent aphthous stomatitis' healing duration differences in female students between the sufferer and non sufferer of chicken pox - Isidora Karsini Soewondo (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2005)
Chicken pox (CP) is a generalized primary infection that occurs the first time an individual contacts the virus. The etiology of CP is a VZV virus, and the replication of virus allowing recovery in two to three weeks. During the process, the VZV may progress along sensory nerves to the sensory ganglia, where it can reside in a latent, undetectable form; and can be reactivated at any time. Recurrent aphthous stomatitis (RAS) is a recurrent ulcer in the mouth, painful, disturbing the mouth's function and esthetic when occurs in the lips. One of the etiology of RAS is the reactivation of the latent virus in the mouth. The aim of this study was to know the contribution of the latent virus in the ganglia, intervered with the differences of the healing duration of RAS in female students, between the CP sufferer and non CP sufferer. By cross-sectionally, clinical examination, after filling the questioner that included informed consent, 307 students of The St. Yusup Senior High School, Karangpilang Surabaya, were examined. In the 3rd class, there were only 6 female students that suffered RAS had CP history, while 11, student did not. Levene's test for equality of variances was done, and p: 0.698, while 2-tail sign: 0.512. According to this statistical analysis, there was no significant difference between the two groups examined. It was suggested that the female students of RAS' sufferer should maintain their balanced food intake, so the ulcer of RAS would heal quickly.